2004
DOI: 10.1111/j.1540-8159.2004.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Site Pacing:

Abstract: Selective site right ventricular pacing has been suggested as an approach to reduce the incidence of ventricular dysfunction and hopefully influence the morbidity resulting from traditional right ventricular apical pacing. Pacing from the right ventricular apex allows a stable ventricular rate, and together with atrial pacing and sensing, helps maintain atrioventricular synchrony but does not allow physiological activation of the left ventricle. Traditional atrial pacing sites like the right atrial appendage m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 20 publications
2
107
0
3
Order By: Relevance
“…18) Additionally, the anatomical accuracy for RV outflow tract is poor and several reports have used inconsistent pacing sites: RV outflow tract free wall or septum. [14][15][16] This has led to procedural difficulties and a risk of complications such as pericardial fluid. 19) The SSP procedure that we introduce in this study enabled safe and accurate positioning of a lead in the RV mid-septum without complications that require a surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18) Additionally, the anatomical accuracy for RV outflow tract is poor and several reports have used inconsistent pacing sites: RV outflow tract free wall or septum. [14][15][16] This has led to procedural difficulties and a risk of complications such as pericardial fluid. 19) The SSP procedure that we introduce in this study enabled safe and accurate positioning of a lead in the RV mid-septum without complications that require a surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] In SSP, His-bundle or para-His pacing 12,13) and a procedure where a ventricular lead is positioned in the RV outflow tract have been used. [14][15][16] The former involves technical difficulties, whereas the latter has produced unsatisfactory longterm effects and also poses a high risk of complications such as pericardial effusion. 17) In this study, we evaluated the efficacy and safety of SSP in patients in whom RV leads were positioned in the middle of the RV septum (mid-septum) and compared it with conventional RV apex pacing.…”
mentioning
confidence: 99%
“…For the second classification, an anteroposterior view and methods modified by Lieberman were used 20 . The RV septum was divided into four areas.…”
Section: Fluoroscopic Definition Of Septal Pacing Sitesmentioning
confidence: 99%
“…However, Schwab et al (Schwaab et al, 2001) have found the detailed mapping of the RV with precise measurements of QRS duration has been found to be impractical. This lack of uniform definitions of where the alternate RV sites actually lie and the inadequacy of tools to consistently reach these locations and verify correct placement may account for the variability in lead positioning within the RVS and may have contributed to the mixed results regarding the long-term hemodynamic benefits of RVS pacing (Lieberman et al, 2004;Balt et al, 2010;Iaizzo et al, 2004). In a recent study, Balt et al (Balt et al, 2010) have concluded that in 143 patients in whom lead implantation in the RVOT was performed, a septal position was achieved in only one-third of patients.…”
Section: Rv Septal Pacing 321 Technical Aspect Of Lead Implantationmentioning
confidence: 99%
“…Indeed from experience, it is very hard to manipulate leads with fluoroscopy at 40° either from the left or right sided approach. However, electrocardiographic criteria such as negative deflection of lead I and positive initial R-waves of the paced ventricular complex in leads II and III ( Schwaab et al, 2001;McGavigan et al,2006;Lieberman et al, 2004;Balt et al, 2010) or the narrowest paced QRS complex available during the mapping of the interventricular septum (Tse et al, 2002;Tse et al, 2009a;Tse et al, 2009b;Schwaab et al, 2001), were not used uniformly. Tse et al and Mera et al (Mera et al, 1999) have postulated that the paced QRS duration is a practical indicator for determining the optimal RV pacing site.…”
Section: Rv Septal Pacing 321 Technical Aspect Of Lead Implantationmentioning
confidence: 99%